Development of a system of motivation for employees of the marketing department of the enterprise for product promotion using tools of informational interaction of virtual space - Raiko, Diana; Shypulina, Yuliia; Vasyltsova, Svitlana; Oborina, Anastasiia; Fedorenko, Irina (PC Тесhnology сеntеr, 2023)
The work considers the problem of developing an approach to increase the motivation of employees of the company's marketing department to promote products (websites) to partners and consumers in the virtual space by using marketing tools of information interaction. Approaches to improving the enterprise management system and increasing its business activity were proposed. The first one is for the formation of well-founded proposals for the development of a system of motivation for marketers in the promotion of products according to the point evaluation system on a certain number of sites where information about the company's activities is posted. The second is to develop recommendations for product promotion by marketers in the virtual space to increase the business activity of the enterprise. Methodical recommendations were proposed, in contrast to the existing approaches, based on the implementation of the motivation system of marketers (link builders and attrichers). Characteristic differences are the substantiation of the employees' motivation to promote the company's products (websites) and the improvement of the structure of the outriggers department. This is due to the introduction of a system of subgroups managed by outriggers under the chairmanship of a team leader. The features that made it possible to solve the mentioned problem are that according to the results of the work of each subgroup, all participants can receive bonuses, motivating each other to work more fruitfully. It was determined that such a system, using the example of outriggers, is the most successful for the sustainable development of the site. The motivation system is used in practice and consists in dividing all the indicators of the site and assigning them the corresponding points, according to the most important criteria. The results are explained by the fact that the better the site's indicators, the higher the score will be given, the higher the bonus will be for the fulfillment or over-fulfillment of the plan by the outreachers. On the other hand, the site will receive better and more diverse links, which is also an important factor for search engines.
Keywords: marketing tools; information interaction; virtual space; website; marketer motivation system